The Sage handbook of workplace learning - Malloch, Margaret [Herausgeber]; Cairns, Len [Herausgeber]; Evans, Karen [Herausgeber]; O'Connor, Bridget N. [Herausgeber] (Sage Publ., 2011)
"This Handbook provides a state-of-the art overview of the field of workplace learning from a global perspective." It "provides a broad-based, yet incisive analysis of the range of theory, research, and practical developments in workplace learning. [...] Key researchers and writers in the field have approached workplaces as the base of learning about work, that is, work-based learning. There has also been emerging interest in variations of this idea such as learning about, through, and at work. Many of the theoretical discussions have centred on adult learning and some on learners managing their own learning, with emphasis on aspects such as communities of practice and self directed learning. In Europe and Australia, early work in the field was often linked to the Vocational Education and Training (VET) traditions with concerns around skills, competencies and 'on the job' learning. The idea that learning and workplaces had more to do with real lifelong and lifewide aspects than traditional 'training' regimens has emerged in the last decade. Since the mid 1990s, the field has grown world-wide as an area of theory, research, and practical work that has not only expanded the interest but has also legitimized the area as a field of study, reflection, and progress." (Verlag, BIBB-Doku)
Keywords: L 3 Lehr-Lern-Forschung; L 2.1.1 Informelles Lernen; L 2.1.3 Erfahrungslernen; L 4.2.3 Internetbasiertes Lernen / E-Learning; G 2.2.4 Lebensbegleitendes & lebenslanges Lernen; Lehr-Lern-Forschung; Lernen am Arbeitsplatz; Lernen und Arbeiten; On-the-job training; Informelles Lernen; Erfahrungsorientiertes Lernen; E-Learning; Lebenslanges Lernen; Internationaler Vergleich